The Effect of Final Income Tax Incentives Rate on the Reporting of PMK 44/2020 Realization Letter - Amelia Oktrivina Siregar; Tryas Chas Biandani; Jihan Khoerunnisa (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2022)
Tax incentives are one of the government's responses to the impact of the COVID-19 pandemic on businesses, and one of the businesses affected by this pandemic is MSMEs. Therefore, this study aims to determine the effect of final income tax incentives borne by the government following PMK No.44/2020, the effect of tax incentives in the form of ease of calculating income tax payable, and the effect of tax incentives in the form of ease of reporting income tax payable to compliance with the reporting of PMK realization letter No.44/2020. This study used primary data by distributing questionnaires to MSMEs in Dramaga Bogor Regency. The data collection method is done by disseminating questionnaires, interviews, and observations. Based on the results of the study, the authors concluded that the final income tax incentive in the form of tax borne by the government has no direct effect, while the tax incentive in the form of ease of calculating income tax payable and tax incentives in the form of ease of reporting income tax directly affects the compliance of PMK reporting No.44/2020.